Brief intervention to reduce fatigue impact in patients with inflammatory arthritis: design and outcomes of a single-arm feasibility study. Issue 7 (18th July 2022) - Dures, Emma; Bridgewater, Susan; Abbott, Bryan; Adams, Jo; Berry, Alice; McCracken, Lance M; Creanor, Siobhan; Hewlett, Sarah; Lomax, Joe; Ndosi, Mwidimi; Thorn, Joanna; Urban, Marie; et al.
Abstract : Objectives: Patients with inflammatory arthritis report that fatigue is challenging to manage. We developed a manualised, one-to-one, cognitive–behavioural intervention, delivered by rheumatology health professionals (RHPs). The Fatigue - Reducing its Effects through individualised support Episodes in Inflammatory Arthritis (FREE-IA) study tested the feasibility of RHP training, intervention delivery and outcome collection ahead of a potential trial of clinical and cost-effectiveness. Methods: In this single-arm feasibility study, eligible patients were ≥18 years, had a clinician-confirmed diagnosis of an inflammatory arthritis and scored ≥6/10 on the Bristol Rheumatoid Arthritis Fatigue (BRAF) Numerical Rating Scale (NRS) Fatigue Effect. Following training, RHPs delivered two to four sessions to participants. Baseline data were collected before the first session (T0) and outcomes at 6 weeks (T1) and 6 months (T2). The proposed primary outcome was fatigue impact (BRAF NRS Fatigue Effect). Secondary outcomes included fatigue severity and coping, disease impact and disability, and measures of therapeutic mechanism (self-efficacy and confidence to manage health). Results: Eight RHPs at five hospitals delivered 113 sessions to 46 participants. Of a potential 138 primary and secondary outcome responses at T0, T1 and T2, there were 13 (9.4%) and 27 (19.6%) missing primary and secondary outcome responses, respectively. Results indicated improvements in all measures except disability, at either T1 or T2, or both. Conclusions: This study showed it was feasible to deliver the intervention, including training RHPs, and recruit and follow-up participants with high retention. While there was no control group, observed within-group improvements suggest potential promise of the intervention and support for a definitive trial to test effectiveness.